Relationship between toxic environmental chemicals, epigenetic factors and Chronic Kidney Disease of unknown etiology in Costa Rica - Montero-Campos, Virginia (Instituto Tecnológico de Costa Rica, 2014)
Conferencia: Relationship between toxic environmental chemicals, epigenetic factors and Chronic Kidney Disease of unknown etiology in Costa Rica, presentada por Virginia Montero Campos del Centro de Investigación en Biotecnología (CIB), de la Escuela de Biología del Instituto Tecnológico de Costa Rica (ITCR).
Conferencia. Instituto Tecnológico de Costa Rica. Escuela de Biología. Centro de Investigación en Biotecnología, 2014
Keywords: Sustancias tóxicas; Compuestos químicos; Enfermedad renal crónica (ERC); Salud pública; Condición ambiental; Etiología (Enfermedades); Agricultor -- Quemas -- Plantas; Regulación -- Agua; Exposición -- Herbicida -- Glifosato; Toxic substances; Chemical compounds; Chronic Kidney Disease (CKD); Public health; Environmental conditions; Etiology (Diseases); Farmer -- Burning -- Plants; Regulation -- Water; Exposure -- Herbicide -- Glyphosate; Research Subject Categories::TECHNOLOGY::Other technology::Environmental engineering; Research Subject Categories::PHARMACY::Toxicology; Research Subject Categories::MEDICINE::Social medicine::Public health medicine research areas